Wilt disease symptoms in red leaf lettuce (Lactuca sativa L.) after inoculated with Trichoderma longibrachiatum - Sazili, Muhammad Iqbal Nul Hakim Mohd; Zakry, Fitri Ab Aziz; Kundat, Franklin Ragai (Update Publishing House, 2022)
Trichoderma is a fungal genus that is widely reported to cause beneficial impacts to crop plants but rarely detriment. The present study was conducted to assess the effect of inoculation of Trichoderma longibrachiatum strain UPMT14 on red leaf lettuce (Lactuca sativa L.) under growth room conditions. A culture of UPMT14 was grown on potato dextrose broth to produce inoculum. This liquid inoculum was injected through the stem of red leaf lettuce seedlings 22 days old with five replications, and then plant growth progress was monitored for vegetative responses. Red leaf lettuce plants began to exhibit foliar symptoms on day 36, such as chlorosis, wilt, and drying out, before total collapsed on day 45 in comparison to untreated control red leaf lettuce plants. In conclusion, the wilting incidence in red leaf lettuce was observed after T. longibrachiatum inoculation. Further studies are needed in future to understand the pathogenesis of T. longibrachiatum.